Challenges of nurse leadership in the context of a health crisis in an international border locality - Gabriela Kauana Silva; Karina Emília dos Santos Scherer; Maria de Lourdes de Almeida (Cogitare Enfermagem)
Objective: To understand the challenges primary health care nurses face regarding their leadership exercise during periods of health crisis in an international border city.